Comparative Study of Local Government Website Quality as Implementation Of E-Government Public Relations in Public Information Disclosure - Wahyu Eka Putri; Ascharisa Mettasatya Afrilia (Universitas Gadjah Mada, 2023)
Law Number 14 of 2008 concerning Public Information Disclosure (UU KIP) has brought logical consequences for all local governments in creating an information climate that is transparent, accurate and easily accessible to the public via the website. Therefore, efforts are needed to improve the quality of websites both in quantity and quality at the local government level. This study aims to determine the quality of the websites of the City Government of Magelang and the Government of Magelang Regency. The research method used is a qualitative method with a comparative approach with a unit of analysis in the form of a number of elements contained in the principle of dialogical communication. The results of the study show that referring to the five elements of dialogic communication, it is known that the Magelang City Government website and the Magelang Regency Government website have fulfilled a number of elements such as information updates, photo availability, and complaint facilities. However, there are still elements that have not been maximized, namely features that are two-way communications.